Growth effect of trade and investment in Sub-Saharan Africa countries: Empirical insight from panel corrected standard error (PCSE) technique - Fredrick Ikpesu; Olusegun Vincent; Olamitunji Dakare (Cogent Economics & Finance, 2019)
The pre-eminence of trade and investment in the economic prosperity of developed and developing countries cannot be overemphasized. Many studies have shown a strong positive impact of trade on economic growth across developed and the emerging market. However, very little is known about the simultaneous effect of trade and investment on growth in SSA when institutional control variables are introduced in the model. Therefore, this study examines the role of trade and investment in the growth process in the SSA using trade openness (% GDP), export (% of GDP) and import (% of GDP) as a measure of trade. We embrace an idiographic perspective that allows methodology and design that are sensitive to the nature of the study by deploying panel corrected standard error (PCSE). In this paper, we draw on 35 countries within the SSA. The research outcomes reveal that trade domestic investment and import affect growth in the region positively while export affects growth negatively. Possible reason for this is the nature of export of sub-Saharan African economies which are mostly affected by price volatility in the global market among other factors such as low prices, vagaries of weather etc. We discuss the policy implication of the study.
Keywords: F1; F10; F11; F14; F43; 330; Growth; investment; trade; sub-Saharan Africa